GUIDE TO THE INTERNATIONAL ARCHIVES AND COLLECTIONS AT THE IISH: SUPPLEMENT OVER 2000 (International review of social history, 2001)
[...]consultation is not restricted; any restrictions are indicated by [notdef].2. Reports of and other documents relating to meetings of the Central Committee and the Central Executive Committee 19901996; documents relating to conferences of the ABSDF 19911996; documents on the political and military policy of the ABSDF; orders by the ABSDF headquarters 19901997; statements; documents on the organization of the ABSDF, including the nancial and health care departments; documents on refugees, the Rodhengar problem, women, human rights violations, the Guide to the International Archives 329 SLORC and other subjects; copies of research papers and other publications by the ABSDF Documentation and Research Centre; news bulletins of the Democratic Voice of Burma (DVB) 19921999; printed material. FEDIP: minutes and other documents of meetings and congresses 1945, 1961, 1965, 1967, 19701973; statutes and rules 1945, 1970; lists of sections n.d.; nancial notes 19601961; correspondence and other documents concerning the campaign for the release of the Spanish prisoners in Karaganda 19471956; correspondence with F. Herzfelder, Felix Martorell, Carlos Martinez Parera, and others concerning indemnity payments to former Spanish prisoners in German concentration camps 19581974; other documents on indemnity payments, including documents concerning the German Bundesentschadigungsgesetz ( BEG) 19541974 and n.d.; reports and notes by Hans Marsalek and others concerning former Spanish prisoners in Mauthausen 1949, 1953, 1957-1971, 1978 and n.d.; lists of names 1946, 1968 and n.d.; documents concerning the Federation Nationale des Deportes et Internes Resistants et Patriotes (FNDIRP) 1968-1970 and n.d.; documents concerning the Federation Internationale Libre des Deportes et Internes de la Resistance (FILDIR) 19641965, 1970 and n.d.; other documents and clippings concerning deported Spaniards in German concentration camps 19391940, 19461972 and n.d. Jose Ester Borras papers: personal correspondence 1937, 19391952, 19571961; identity cards and other personal documents 1931, 1937, 19451947, 1952 and n.d.; typescript of `Recuerdos y Reejos', rst chapter of his autobiography 1942; documents on the French resistance and the liberation of Paris 1941, 19451946, 1948, 1959, 1966 and n.d.; documents from his wife Odette Ester-Kervorc'k 1976 330 Guide to the International Archives 1992 and n.d. CNT in exile: minutes of meetings 19481949; correspondence with A. Germinal Esgleas of the Movimiento Libertario Espanol (MLE) 19471948 and correspondence with Marcelino Massana 1951-1952, Jose Peirats 1951 and n.d., Roque Santamaria 19511952 and others 19451974; les concerning persons, including Juan Cazorla Pedrero 19521954; Luis Companys 1934, 1936, 1940, 19691970; Guillermo Farregut Castells 1950 and n.d.; A. Florentino Estallo 19521955; Gabriel Garcia Tomas 19491950; Manuel Mendez de Vigo y Cubas n.d.; Quintin Sanchez 1952; Francisco Sanz 1950 and n.d.; Felipe Torrente Larrosa 19521953; les on the weekly Ruta of the Federacion Iberica de Juventudes Libertarias (FIJL) in France 1953, on interventions in behalf of prisoners in Spain and France 19461947, 1949, 1952, on the exile of inhabitants from Berga in France 194719511953, 19571960, 1966 and other subjects; reports, notes and other documents concerning the CNT 19461952, 1966 and n.d.; typescripts of articles by J. Ester 1941, 1943; printed material, including photocopies of newspaper articles by Albert Camus on the Franco regime in Spain 19481953, 1957, 1959, 19611962, 19641966 and n.d. Gulf Peace Team Period: 19901992Size: 1 m.The Gulf Peace Team was an international organization aiming at peace and justice in the Middle East through nonviolent means; headquarters in London and Amman, Jordan; activities were the issuing of a newsletter and the organizing of peace walks in the Middle East. A series of chronological notes on the political history of Pakistan by Ahmad Saleem 19471969, 19711977; a series of documents relating to political parties and politicians collected by Ahmad Saleem, including his supplementary notes 1947 1969, 19711977; congress papers, manifestos, leaets, newsletters, copies of periodicals and other documents relating to the Communist Party of Pakistan (CPP) 1975, 19811988, 19992000, the East Pakistan Awami League 1966, 1969, the Kalat State National Party 1947, the Labour Party Pakistan 19982000, the Mazdoor Kisan Party (MKP) 19721975, the Communist Mazdoor Kisan Party (originated from a merger with the CPP) 19982000, the National Awami Party 19661970, the Pakistan Peoples Party (PPP), 19701974, 19871988, 1990, 1992, 1994, the Pakistan Socialist Party 19881999, the Young Peoples' Front 19701973 and other political organizations; documents relating to trade unions, the student movement and the peasant movement; booklets, pamphlets and other printed material, including the secret `Punjab political Who's Who' 1921 and a series of government intelligence reports on the 1947 massacres of Muslims (published in 1948); personal documents consisting of manuscripts of poems by Sara Shagufta, a manuscript by Iqbal Leghari on the history of the socialist movement in Pakistan, an autobiographical account by Fazal Ilahi Qurbun, some documents of Hyder Baksh Jatoi 19681969, documents of S.M. Jaffar, Director of Archives of the North-West Frontier Province 1931, 19351974 and director of the Peshawar Museum, consisting of correspondence with historians, librarians, and others 19641973; completed questionnaires and other documents.